2011
DOI: 10.1007/s12524-011-0102-6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Application of Optical and Radar Data for Archaeological Exploration in the Talakadu Region, Karnataka

Abstract: Talakadu is a well known historic place

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition to the use of FCCs and SAR data, this study was also supported by the digital elevation models generated using SRTM DEM. SAR imagery also revealed a palaeochannel adjacent to the site Talakadu near Mysuru 20 . Field observations showed agricultural land along this channel, which gets flooded during heavy rains (Figure 3).…”
Section: Indirect Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the use of FCCs and SAR data, this study was also supported by the digital elevation models generated using SRTM DEM. SAR imagery also revealed a palaeochannel adjacent to the site Talakadu near Mysuru 20 . Field observations showed agricultural land along this channel, which gets flooded during heavy rains (Figure 3).…”
Section: Indirect Signaturesmentioning
confidence: 99%
“…They are statistical in nature, with a certain mean value and some dispersion around it. The effects of polarization in analysing archaeological landscapes have been studied by Holcomb and Shingiray 19 and Rajani et al 20 .…”
Section: Other Dimensions Of Signatures and Their Interpretationmentioning
confidence: 99%
“…Satellite images have also been used to investigate ritual spaces and cultural landscapes 10 . Integrated applications of satellite imagery, GPS and GIS in India has been carried out for Nalanda 11 , Hampi 12 and Talakadu 13 as pilot case studies.…”
Section: Remote Sensing and Gis Applications In Archaeologymentioning
confidence: 99%
“…Paleodrainage network of western Rajasthan has been reconstructed using multi-sensor satellite data (radar as well optical sensors) and GIS techniques 23 . A buried channel near the archeological site of Talakadu, Mysore, Karnataka situated on banks of River Cauvery was revealed by analysis of RADARSAT-1 C band VV polarization data 24 . These studies demonstrated the potential of radar data in detecting hitherto unknown features of geoarchaeological significance.…”
Section: Introductionmentioning
confidence: 99%